The professional careers of former Portuguese football players: a sociodemographic and professional approach - Eduardo Teixeira; Carlos Silva; Félix Romero; Mauro Miguel; António Vicente (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: The study is aimed to identify sociodemographic and professional characteristics related to the careers of former Portuguese football players.